Baltic economic reforms: A crisis review of baltic economic policy - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2010)
The Baltic economies were severely hit by the global financial crisis. Gross Domestic Product has contracted considerably. Naturally, it asked what went wrong with the "Baltic economic model". This paper surveys the programme of comprehensive economic reforms in the Baltic countries (the case of Estonia serves as the "lead story") post independence. It gives particular weight to reforms of the macro economy and trade policy, and to the privatisation programme. It concludes, firstly, that the Baltic countries opted for the right set of institutional economic structures at the time of independence. It was also a good economic strategy to speed up reforms. In contrast to many other transition countries in Europe, the Baltic countries had been part of the Soviet Union and had to go through a much tougher reform period. They had to quickly leave the rouble zone and the structure of economic planning inside the Soviet Union. Other transition countries, like Poland, had in this respect a much easier task. Secondly, as the Baltic economies matured and entered the European Union, the passion for continued economic reforms slowed down markedly. Too many people believed they could keep climbing in wealth without the pain of economic and behavioural change. Accession to the European Union was the crowning of the past reform period. Some thought it to be the end of the reform period. Thirdly, as the economies matured, there should ideally have been a shift in some macroeconomic policies to help cool economies that were overheating and building up asset bubbles. Lastly, the proper economic policy strategy for the Baltic countries now is to entrench its economic policy integration with Europe.
Keywords: B24; E02; F13; L53; P20; 330; Baltic economic development; transition; structural reform; financial crisis; Wirtschaftspolitik; Wirtschaftswachstum; Systemtransformation; Finanzkrise; Estland; Euroregion Baltik